The Relationship Between The Physical Condition Of The House And Smoking Habits With The Incidence Of Acute Respiratory Infections In Toddlers In The Work Area Of The Rambah Health Center In 2022: Hubungan Kondisi Fisik Rumah Dan Kebiasaan Merokok Anggota Keluarga Dengan Kejadian Ispa Pada Balita Di Wilayah Kejra Puskesmas Rambah Tahun 2022 - Sulistina Sulistina; Kamali Zaman; Sri Desfita; Reno Renaldi; Benny Yulianto (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Acute respiratory infektion (ARI) Are Infections of the upper and lower respiratory tract caused by viruses, fungi and bacteria. The candition of the home environment that has not met the requirements and the smoking habits of family members in the hous are, factors in the insidence of ARI toddlers in Rambah Tengah Hulu. The purpouse of this studi was to determini the relationship between physical home factors and smoking habits of family member with the insidence of ARI among children under Rambah Tengah Hulu. This type of research is quantitative using a cross sectional study design. Conducting interviews, observation and house measurements, namely house ventilation and house humidity with total sample of 100 respondents using the Purvosif sampling technique. The subjek of this study were monthers of toddlers 0-24 months. The research was conducted in Rambah Tengah Hulu in februare- march 2022. Data analysis was carried out unnivariate and bivariate using the Chi Square test with a 90% degree of confidence. From the results of research and discussion it can be concluded that of the 5 variabels all there is a relationship between the area of house ventilation pvalue = 0,049 ( α 0,05 ), Use of cooking fuel = 0,0013 ( α 0,005), Occupancy density Pvalue= 0,000 ( α 0,05), Smoking habits of family members Pvalue= 0,008 (α 0,05), Use of mosquito coils Pvalue= 0,008 (α 0,05) Whit the incidence of ari in toddlers in Rambah Tengah Hulu in 2022. The results of this study are expected to provide prevention and control for the community and can be used as a reference for knowing physical factors of the house and smoking habits of family members that cause ARI in toddlers.